Design and gender studies: experience of a mass subject at the University of Buenos Aires - Flesler, Griselda; Durán, Valeria; Moretti, Celeste (RChD: creación y pensamiento, 2023)
The demands around gender policies at the university can be problematized from three dimensions related to knowledge, sociability between different institutional actors, and transformations in spaces. From this perspective, this article proposes to focus on an experience transited in recent years at the University of Buenos Aires: the creation in 2017 of the subject Design and Gender Studies in the Faculty of Architecture, Design and Urbanism. Starting from the premise that the feminist perspective is not only content to be taught but also—and perhaps fundamentally—a practice, the subject does not split form from content. In this sense, the pedagogy of the subject takes three fundamental pillars: openness, transdisciplinarity, and care. The actions and collaborations described in this writing show the challenges, tensions and resistances that it entails. In this case, feminist teaching in the field of design could be possible through the consolidation of ties and commitments of different actors in the university community (authorities, teachers, students and administrative, and maintenance workers).